Incidence and factors associated with acute kidney injury (AKI) in hyperchloremic critically III adult patients - Hisham, Wan Mohd Hafidz Wan (2019)
Hyperchloremia is still the least looked at electrolytes imbalance in ICU despite a few studies in the last decade has proven its association with AKI. This study is aimed to report on the incidence and factors associated with AKI in hyperchloremic critically ill adult patients. Methods In this retrospective cohort study held in a tertiary hospital, hyperchloremic patients aged 18-65 years old on admission were included. Development of AKI using AKIN criteria within the next 48 hours was marked as the primary outcome and factors associated with it were analysed. Results 248 (11.7%) of the patients admitted during the study were hyperchloremic on admission. Out of this, 84 (34%) patients developed AKI. Age 56-65 years [OR=2.598 (1.126-5.995); p=0.025], SAPS II score [OR=1.04 (1.02-1.06); p<0.001], respiratory failure [OR=2.516 (1.064-5.947); p=0.036], cardiovascular failure [OR=2.239 (1.083-4.626); p=0.030], severe hyperchloremia[OR=2.045 (1.176-3.557); p=0.011], severe acidemia [OR=2.733 (1.269-5.886); p=0.010] and severe metabolic acidosis[OR=2.003 (1.010-3.972);p=0.047] were found to be associated with AKI. After adjusting to confounding factors, SAPS II score (adjusted OR, 1.032 [1.003-1.062]; p=0.028) and age 56-65 years (adjusted OR, 2.506 [1.024-6.135]; p=0.044) were found to be predictive of AKI. Conclusions One-third of hyperchloremic patients developed AKI after 48 hours of ICU admission. SAPS II score and age group 55-65 years are proven to be predictive factors of later development of AKI. SAPS II score is a useful tool in predicting AKI in hyperchloremic patients.